Structural and Electronic Properties of Adenine-Thymine Basepair : A Computational Study (Dhaka University Journal of Science, 2019)
It is well known that stability of deoxyribo-nucleic acid (DNA) double helix depends on hydrogen bonding (HB) between adenine-thymine and guanine-cytosine. HB plays an important role in molecular systems, particularly in biological systems because all lives on the earth may be viewed as a matter of hydrogen-bonding supramolecular systems. Since HBs have a central role on the mechanism of life phenomena including the structure and functions, it is essential to understand the molecular-level aspects of HB systems. Therefore, we studied the structural properties of adenine-thymine (A-T) basepair theoretically using DFT/B3LYP/6-31G level of theory. Theoretically we found four isomers of A-T basepair and the most stable isomer is one in which adenine and thymine are connected via two hydrogen bonding. The electronic properties were calculated by Time Dependent Density Functional Theory (TD-DFT) approach.Dhaka Univ. J. Sci. 67(1): 51-54, 2019 (January)